Perception, Experience, Attitude and Satisfaction on Using Information and Communication Technology-Based Teaching-Learning Activities in Medical Program (Sir Salimullah Medical College Journal, 2022)
Background: Educational innovation is moving from a fully traditional system to an innovative and interactive teaching method, inspiring our students for self-directed learning, concentrating on quality improvement, trying to mold the curriculum and evaluation system. Using Information and communication technology (ICT) in education is not to replace the traditional method, but to complement it.Objective: To study the undergraduate students’ attitude, experience and satisfaction regarding use of technology for teaching-learning, within E-learning Environments that is the Requirement of individual ICT infrastructure for the institutions, also the MlearningMaterials and Methods: Online questionnaire survey on 41 students of a batch in 4th year of SSMC on Google format was done to understand their ICT experiences and acceptance towards the tools in COVID pandemic mainly focused on M-learning, a part of E-learning. Moving out of the traditional system, a power point presentation was shared with the students through mail. They downloaded it in their smartphone, gone through it as a selflearning content to their exam. After their exam this survey was done. The data was collected online and automatically showed in pie charts.Results: Among the 41 students 41(100%) have got the personal handle held tools. But still, out of their online classes they use these tools for educational purposes in this manner- 61% spends 25-50%, 22% spends 50-75% and 17.1% spends 10-25% of their total usage period. 68.3% students prefer video as a content, 17.1% as PDF and 7.3% as power point presentation. Due to advancement of the ICT tools 73.2% did not face any difficulty in receiving and reading the content. Degree of satisfaction was done through a 4-point Likert scale online. 26.8% were well satisfied, 43.9% were satisfied and 29.3% showed average in their response. All the students 41(100%) showed their interest on having same type of learning in future.Conclusion: ICT influences our teaching learning system, which has a great prospect. Changes in this system is needed to get the benefit from ICT tools exclusively in future.Sir Salimullah Med Coll J 2022; 30: 29-34